Targeted Temperature Management for In-hospital Cardiac Arrest Caused by Thyroid Storm: A Case Report - Fu, Yuanwei; Ge, Hongxia; Zhang, Yumei; Li, Yan; Mu, Bingyao; Shang, Wen; Li, Shu; Ma, Qingbian (Frontiers in Cardiovascular Medicine, 2021)
Background: Malignant ventricular arrhythmias caused by thyroid storm, such as ventricular tachycardia (VT) or ventricular fibrillation (VF), which are life-threatening, are rare. We report the case of a patient who suffered from cardiac arrest caused by thyroid storm and the rare VF; the patient showed a favorable neurologic outcome after receiving targeted temperature management (TTM) treatment by intravascular cooling measures. Case presentation: A 24-year-old woman who had lost 20 kg in the preceding 2 months presented to the emergency department with diarrhea, vomiting, fever, and tachycardia. Thyroid function testing showed increased free triiodothyronine (FT3) and free thyroxine (FT4), decreased thyroid-stimulating hormone (TSH), and positive TSH-receptor antibody (TRAB). She was diagnosed with hyperthyroidism and had experienced sudden cardiac arrest (SCA) due to ventricular fibrillation (VF) caused by thyroid storm. The patient was performed with targeted temperature management (TTM) by intravascular cooling measures. Regular follow-up in the endocrinology department showed a good outcome. Conclusions: Our case not only suggests a new method of cooling treatment for thyroid storm, but also provides evidence for the success of TTM on patients resuscitated from in-hospital cardiac arrest (IHCA) who remain comatose after return of spontaneous circulation (ROSC).